Secondary science teachers' implementation of a curricular intervention when teaching with global climate models. Issue 4 (11th October 2022) - Carroll Steward, Kimberly; Bhattacharya, Devarati; Chandler, Mark; Forbes, Cory T.
Abstract: In the past decade, emphasis on promoting "climate literacy" in K-16 science classrooms has increased. Teachers play a critical role in cultivating these opportunities, especially in secondary science classrooms. However, most prior climate education research has focused on students and student learning; little is known about how teachers implement climate-focused curricular interventions. Here, we report findings from a concurrent mixed methods, multiple-case study of four secondary science teachers' implementation of a new, NGSS-aligned, model-centric climate curriculum module grounded in the use of a data-driven, computer-based climate modeling tool—Easy Global Climate Model (EzGCM). We employ multiple data sources, including video-recorded classroom observations, interviews, and instructional artifacts, and both qualitative and quantitative analyses, to investigate how teachers implemented the curriculum. Findings show that, overall, teachers implemented the curriculum in ways that were less model-centric than designed, placing greater emphasis on EzGCM itself rather than using the model to investigate Earth's changing climate. Additionally, we present detailed single-case studies of each participant teacher that highlight differences in teachers' implementation of the curriculum module and their reasoning for making observed instructional decisions. This research sheds light on the design of secondary science learning environments by illustrating the varied ways teachers implement a climate-focused curriculum to support students' developing climate literacy. This has important implications for the design of climate-focused curriculum and supports for teachers.